ANALISIS STRATEGI PENJUALAN TAHU SUSUN DALAM MENINGKATKAN PRODUKSI TAHU DI DESA LALANGON KECAMATAN MANDING - Muhammad Ilham Cholif; Very Andrianingsih (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
The problem studied in this thesis is about the sales strategy of stacked tofu in increasing tofu production at the tofu factory in Lalangon Village, Manding District. With the aim of knowing the sales strategy of Tofu at the Tofu Factory, Lalangon Village, Manding District, Sumenep Regency. In determining the strategy, the researcher uses a SWOT analysis by knowing the internal environment (strengths and weaknesses) and the external environment (opportunities and threats). The type of research in this study is to use a qualitative research type with the informants of the Lalangon Village Tofu factory owner, the Production section, Traders, and consumers. The research instrument was carried out by observation, interviews and documentation. The data analysis used is SWOT analysis. The results showed that the analysis of the internal environment had the strength of its own capital, business experience in the field of tofu, good relations between entrepreneurs, short distribution lines, good quality of tofu, guaranteed production continuity. Meanwhile, the weaknesses are limited working capital, low education level, no product diversity, limited promotion, less hygienic management of tofu, not evaluating and monitoring properly, waste management is not optimal. In external conditions, the opportunities that are owned are the attention from the government, there is trust from consumers, the continuity of raw materials is guaranteed, traders help expand marketing. Meanwhile, the threats are a complicated process to get capital from the cooperative service, competition in the quality and quantity of tofu between tofu factories, fluctuations in raw materials, etc. Strategies that can be applied are maintaining product quality by utilizing technological developments to maintain consumer confidence, improving the quality of human resources through programs from the government, establishing partnerships to improve marketing efficiency and using simple SOPs for effectiveness and efficiency.